2009
DOI: 10.1002/cctc.200900070
|View full text |Cite
|
Sign up to set email alerts
|

Alumina‐Supported Ni–Au: Surface Synergistic Effects in Catalytic Hydrodechlorination

Abstract: Catalytic gas‐phase hydrodechlorination (HDC) of 2,4‐dichlorophenol (2,4‐DCP) has been investigated over Ni/Al2O3 and Au/Al2O3 prepared by impregnation, and Au–Ni/Al2O3 prepared by reductive deposition of Au onto Ni. Catalyst activation by temperature‐programmed reduction is examined and the activated catalysts are characterized in terms of H2 chemisorption, XRD and TEM‐energy dispersive X‐ray (EDX) measurements. Ni/Al2O3 (<1–10 nm) and Au/Al2O3 (<1–15 nm) exhibit a relatively narrow metal size distribution wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 71 publications
2
32
1
Order By: Relevance
“…The similar shape was observed for NiO particles immobilized on TiO 2 , ZnO, and ZrO 2 ( Table 1). The obtained results are in agreement with the shape of nickel particles immobilized by impregnation from the aqueous solution of Ni(NO 3 ) 2 [9].…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…The similar shape was observed for NiO particles immobilized on TiO 2 , ZnO, and ZrO 2 ( Table 1). The obtained results are in agreement with the shape of nickel particles immobilized by impregnation from the aqueous solution of Ni(NO 3 ) 2 [9].…”
Section: Resultssupporting
confidence: 86%
“…The rate-determining step in hydrogenation is usually a dissociative adsorption of H 2 that takes place at Ni 0 sites not at Ni 2+ [4]. Keane and Medina showed that large NiO clusters are reduced much easier to Ni 0 in comparison with small NiO clusters that strongly interact with surface groups of the support [9,27]. Therefore, the 7 nm NiO of the sample №s 8 and 11 possess higher activity in hydrogenation in comparison with the 3 and 4.5 nm NiO of the sample № 3 and № 5 ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations